The politics of everyday life in Gĩkũyũ popular music of Kenya (1990-2000) - Maina Wa Mũtonya ([publisher not identified], 2014)
While probing the politics of everyday in Gikuyu popular music, the main thrust of this book is to unpack the representation of daily struggles through music. Depending mainly on the lyrics of the songs, the study also combines both the textual and the contextual analysis of the music. Music here is studied both as a text, and as an aspect of popular culture. The decade 1990-2000 in Kenya provides two contrasting political developments, which directly impacted on the ordinary Kenyan; firstly, the extremes of the country's one-party rule were at the peak until when multi-party democracy was re-introduced. This ushered in a new era, but with antecedents in one-party rule, where service delivery was below par and economic mismanagement, corruption, assassinations and detentions continued unabated. It is in this contrasting environment that popular arts proliferated as a way of countering the repressed freedom of expression. This book, therefore, looks at how the Gikuyu musicians reacted and responded to these social and political realities in their songs. Music is discussed as an essential site for creation, re-creation and negotiation of the various forms of identities.